DIVERSITY: FORTUNE OR MISFORTUNE? - Agus Raharjo (Jurnal Dinamika Hukum, 2017)
Anthropologically, Indonesia is rich of diversities. It occupies the largest ethnic groups of the world. On the one hand, diversity is viewed as wealth, pride and goal for other countries to learn tolerance. On the other hand, it is actually latent potentials for national disintegration......